Evaluation of Johnson County Kansas Healthcare Provders' Knowledge of the Johnson County Health Departments' Public Health Emergency Preparedness and Response Program and Utilization of the Data to Create an Emergency Contact Database - Olson, Danyel (My University, 2010)
The American Medical Association (AMA) and the American Public Health Association (APHA) have realized the need for collaboration between medicine and public health. Many initiatives have been started to examine the benefits of these two groups working together. Numerous panels have convened to analyze findings collected from focus groups made up of practitioners and students studying public health throughout the United States. Federally funded grants with goals specified by the Centers for Disease Control and Prevention have been distributed to numerous public health programs. The two objectives for this project were 1) Evaluate the Johnson County medical community’s awareness of the Johnson County Public Health Emergency Preparedness and Response Programs existence and 2) Gather pertinent contact information from the medical community to create an emergency contact database. To effectively achieve these objectives, specific goals needed to be addressed: 1) Meeting the federally funded goals specified by the Centers for Disease Control and Prevention Bioterrorism Grant, 2) Developing communications and interactions between the Johnson County medical community and the Johnson County Public Health and Emergency Preparedness and Response Program, 3) Determining the level of familiarity the Johnson County medical community has with the Public Health Emergency Preparedness and Response Program, 4) Analyzing data collected to help establish guidelines for future educational programs and 5) Obtaining pertinent contact information from Johnson County medical providers to create a database to be utilized during emergency. The components of this project are: the creation of an introductory letter and a questionnaire to be mailed to the Johnson County medical community, obtaining a current mailing list of all the medical providers (physicians, nurses, veterinarians, pharmacists) in Johnson County, formulating a mailing schedule, developing a usable database for keeping track of questionnaire responses, analyzing data collected to provide insight for future educational programs, and producing and populating a workable database to house contact information for the medical providers wanting to participate in the emergency contact resource. The results of the survey showed that there is interest in these groups working together but there is still a lot of work needing to be done to facilitate this happening.
Keywords: Public health emergency; Medical community; Questionnaire; Collaboration; Preparedness; Initiatives; Health Sciences, Public Health (0573)